Surface activity of surfactin recovered and purified from fermentation broth using a two-step Ultrafiltration (Uf) Process - Mohd. Hafez Mohd Isa; Richard Frazier .A; Paula Jauregi (Universiti Kebangsaan Malaysia, 2011)
B. subtilis under certain types of media and fermentation conditions can produce surfactin, a biosurfactant which belongs to the lipopeptide class. Surfactin has exceptional surfactant activity, and exhibits some interesting biological characteristics such as antibacterial activity, antitumoral activity against ascites carcinoma cells, and a hypocholesterolemic activity that inhibits cAMP phosphodiesterase, as well as having anti-HIV properties. A cost effective recovery and purification of surfactin from fermentation broth using a two-step ultrafiltration (UF) process has been developed in order to reduce the cost of surfactin production. In this study, competitive adsorption of surfactin and proteins at the air-water interface was studied using surface pressure measurements. Small volumes of bovine serum albumin (BSA) and β-casein solutions were added to the air-water interface on a Langmuir trough and allowed to stabilise before the addition of surfactin to the subphase. Contrasting interfacial behaviour of proteins was observed with β-casein showing faster initial adsorption compared to BSA. On introduction of surfactin both proteins were displaced but a longer time were taken to displace β-casein. Overall the results showed surfactin were highly surface-active by forming a β-sheet structure at the air-water interface after reaching its critical micelle concentration (CMC) and were effective in removing both protein films, which can be explained following the orogenic mechanism. Results showed that the two-step UF process was effective to achieve high purity and fully functional surfactin.